Lizards from Estação Ecológica de Santa Bárbara, a remnant of Cerrado in the state of São Paulo, Brazil - Araujo, Cybele O.; Maffei, Fábio [UNESP]; Corrêa, Décio T.; Moya, Guilherme M.; Nascimento, Bruno T. M. [UNESP]; Santos, Selma Maria A. (Pensoft Publishers, 2014)
Although the reptile fauna in the state of São Paulo is the best known in Brazil, there are still important sampling gaps, especially within the natural remnants of the Cerrado. Only 0.5% of this region is protected in the state, and the remaining fragments suffer threats that include risk of extinctions due to fragment isolation, risk of fire, and invasion by exotic plant species. In this study, we provide information on lizard diversity from the Estação Ecológica de Santa Bárbara, one of the few remaining remnants of Cerrado in the state of São Paulo. We sampled lizards using pitfall traps monthly from October 2008 to March 2009 and October 2011 to November 2012. We recorded 12 lizard species from nine genera and five families (Gymnophthalmidae, Polychrotidae, Scincidae, Teiidae, and Tropiduridae). Our study expands the knowledge about lizard diversity in the Brazilian Cerrado, a global biodiversity hotspot.